PORTFOLIO OPTIMIZATION MODELING IN THE CONSUMER GOODS INDUSTRY - Muthia Ulfa; Ahmad Fauzi Amrullah; Laksmi Ayudyanti; Harry Patria (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Portfolio optimization refers to the process of choosing the proportions of assets to be placed in a portfolio. The objective of this research is to analyze the performance of various portfolio optimization models. This study uses Statistical Calculation R software to analyze the performance of portfolio optimization models, including Monte Carlo with Sharpe Ratio. We will analyze the multi-asset data of the 5 con-stituent consumer goods stocks listed on the Indonesia Stock Exchange (IDX) for 1 year and a half. Then use R to test the stock performance of the model. By using additional risk indicator to assess equity performance, such as volatility, Sharpe ra-tio (SR), risk parity (RP) the result shows that ICBP.JK with 41.5% SR and 28.1% RP that could be a recommendation to invest stocks in this consumer goods industry.